Kardiochirurgia dorosłychOwn experience in valve-sparing aortic root repair with single Dacron patch technique - Borzymowski, Jan; Przybylski, Roman; Łoś, Joanna; Urbanski, Paul; Pasek, Piotr; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
For patients qualified for operation because of aneurysm of the ascending aorta combined with aortic valve insufficiency we can offer valve-sparing aortic root reconstruction, which lets them avoid chronic antithrombotic therapy and significantly decreases the risk of side effects in the distant postoperative course. Valve-sparing aortic root repair with patch technique and the use of ascending aorta prosthesis is gaining acceptance as a safe method of aortic root reconstruction for durable and efficient effect, both in the postoperative and the distant course. This technique is especially advantageous in patients with aortic root asymmetry, or patients in whom reconstruction of all Valsalva sinuses is not needed.